Characteristics of 2.5 MV beam and imaging dose to patients. Issue 3 (December 2017) - Ding, George X.; Munro, Peter
Abstract: Purpose: This work provides the beam characteristics and evaluates the imaging dose to patients for a 2.5 MV portal imaging beam. Method and materials: The Monte Carlo technique has been used to simulate the 2.5 MV imaging beam. Beam characteristics have been analyzed including the energy spectra and the fluence distributions as a function of position away from the beam central axis. The accuracy of a simulated beam was validated through comparisons between the Monte Carlo calculated and measured dose distributions in a water phantom. The simulated 2.5 MV beam was also used to obtain the absorbed-dose beam quality conversion factor, kQ, for absorbed dose calibration. The simulated beams were then used to evaluate the imaging dose to patients compared with that from a conventional therapeutic 6 MV beam. Results: The mean energies of photons and electrons in the 2.5 MV beam are 0.48 MeV and 0.37 MeV respectively. The photon fluence decreases at 20 cm away from the central axis by only up to 30% for this flattening-filter free beam. The values of % dd curves at depth = 10 cm are 53% and 63% for 10 × 10 cm 2 and 40 × 40 cm 2 fields respectively. Portal imaging doses (D50 of the DVHs) to the eyes, heart and bladder from representative pairs of 2.5 MV (or 6 MV) setup images are 1.8 cGy (3.5 cGy), 1.1 cGy (2.5 cGy) and 1.0 cGy (2.4 cGy) for head, thorax and pelvis image acquisitions respectively. Conclusion: We provide dosimetric data, as well as estimates of organ imaging doses, for this 2.5 MV beam. When clinical default imaging protocols are used, the imaging dose from the 2.5 MV beam is about 50% of that from a 6 MV beam. The information can be used to select image procedures and to estimate organ dose from imaging procedures.